Penguatan Whistleblowing System di Indonesia (Studi Kasus Whistleblowing System di Badan Pemeriksa Keuangan Republik Indonesia (BPK RI)) - Ni Putu Bayu Widhi Antari (Public Inspiration : Jurnal Administrasi Publik, 2020)
Whistleblowing system is one of essential elements to protect integrity and accountability of public sector organization. Audit Board of Indonesia is one of institutions which is vulnerable on illegal and unethical behaviours in carrying out their authorities because the audit results can be a source investigation if there is an illegal or unethical behaviour. This research aims to describe the enablers and inhibitors of being whistleblower and explain the strategic ways to strengthen the whistleblowing system. This research utilized interpretivism as the research approach and carried out observation and literature study as data collection method. The former auditor of the Audit Board of Indonesia wanted to be a whistleblower because of auditor’s belief that his report will be followed up, good cooperation between the Corruption Eradication Commission (KPK) and The Audit Board of Indonesia, appreciation from international agency, and economic incentive. Nevertheless, low level of legal protection cause reluctance to be whistleblower. Whistleblowing system can be strengthened by developing supportive legal framework and organizational culture on whistleblowing.